Method for preparing heat-conducting substrate by compounding micro-powder diamond and copper

Through microwave plasma reduction and regulation of molten salt technology, the problem of difficult and high cost of metallization of micropowder diamond surface is solved, and a micropowder diamond copper composite substrate with high thermal conductivity and low cost is prepared.

CN119753404APending Publication Date: 2025-04-04HANGZHOU DIANZI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411817142.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has high cost and difficulty in metallizing the surface of micropowder diamond in preparing micropowder diamonds, which limits its application.

Method used

Micropowder diamond was reduced by microwave plasma and the molten salt process was regulated, and micropowder diamond particles with high surface metal layer coating rate were successfully obtained, and thermally conductive substrates were prepared in combination with copper powder.

Benefits of technology

It achieves the reduction of product density and cost while maintaining high thermal conductivity, and expands its practical application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753404A_ABST
    Figure CN119753404A_ABST
Patent Text Reader

Abstract

The invention relates to a process for preparing a heat-conducting substrate by compounding micro-powder diamond (irregular in shape) and copper powder. The invention aims to provide a solution for solving the problem of heat dissipation of electronic components caused by current artificial intelligence updating and performance improvement of high-power devices. The morphology, the thickness and the like of a carbonized layer on the surface of the micro-powder diamond are regulated and controlled by regulating and controlling the time and the temperature of the molten salt method and the proportion of diamond to metal powder in molten salt. And changing the volume ratio of the micro-powder diamond in the composite substrate to obtain an optimal solution of the volume ratio. The micro-powder diamond subjected to surface metallization is fully mixed with the copper powder, the composite substrate is prepared by adopting a vacuum hot pressing method after pre-compression molding in a mold, the process has the advantages of being easy to operate, low in cost, capable of being prepared in batches and the like, and the application range of the diamond-copper composite material in the aspect of precise electronic packaging is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a heat-conducting substrate by compounding micro-powder diamond and copper, and belongs to the field of electronic packaging, heat sink substrate and thermal management material technology. Background Art

[0002] Diamond copper composites are made by adding diamond particles with high thermal conductivity and low expansion coefficient to Cu with good ductility and thermal conductivity, and at the same time have high thermal conductivity and adjustable thermal expansion coefficient. Currently, in the fields of high-power insulated gate bipolar transistors (IGBT), microwave, electromagnetic, optoelectronic devices, and high-energy solid-state lasers and other national defense technologies, there is an urgent need for a fourth-generation thermal management material with high thermal conductivity.

[0003] The non-wetting property between diamond particles and copper and the mismatch of phonons are obstacles to the high thermal conductivity of diamond-copper composite materials. Currently, researchers are solving the non-wettability between diamond and copper from two aspects: metallization of diamond surface and alloying of copper matrix. Some researchers use magnetron sputtering to coat the diamond surface with transition metals and obtain a metal carbide layer after annealing. This method requires subsequent treatment after plating to obtain a metal carbide layer, which is relatively cumbersome. Some researchers also use alloying of copper matrix to solve the non-wettability between diamond and copper, but this method has high requirements on equipment and a long production cycle. The molten salt method is used to obtain surface metallized diamond, and then prepare a composite substrate with copper. This method is simple to operate and low in cost, and after adjusting the process, a diamond-copper composite substrate with good overall performance can be obtained.

[0004] When researchers prepare diamond copper composite substrates by molten salt method and study their related properties, they mostly use MBD6 diamonds, which are of higher quality. Their production process is complex and costly. The low yield of MBD6 diamonds leads to a further increase in the price of MBD6 diamonds, which in turn increases the production cost of diamond copper composite substrates. Therefore, the existing technology of preparing diamond copper composite substrates by molten salt method has the problem of high cost.

[0005] Micro-powder diamond is the waste material obtained by cutting regular diamonds such as MBD6 diamonds when preparing regular diamonds. Micro-powder diamonds are irregular in shape, with dense grooves on the surface, and no crystal faces of MBD6 diamonds. The waste can be passed through a sieve to obtain 10μm to 30μm micro-powder diamonds. The use of micro-powder diamonds to prepare micro-powder diamond copper composite substrates can reduce costs while having high thermal conductivity, and can well meet the heat dissipation needs of multiple fields and reduce their costs. Due to the small particle size of micro-powder diamonds and their irregular shape, the surface metallization of micro-powder diamonds is more difficult, which limits the application of micro-powder diamonds in the preparation of micro-powder diamond copper composite substrates. Summary of the invention

[0006] The micro-powder diamond of the present invention is a special diamond different from the conventional MBD6 diamond, which is the waste material cut off when preparing MBD6 diamond and other regular diamonds. There are a large number of uneven parts and gullies on the surface, no specific regular shape; and no special crystal plane of conventional MBD6 diamond.

[0007] In order to overcome the shortcomings of the existing technology in terms of cost and surface metallization of micro-powder diamond, the invention uses microwave plasma to reduce micro-powder diamond and then regulates the molten salt process to successfully obtain micro-powder diamond particles with a high surface metal layer coverage rate. Then, it is compounded with copper powder to prepare a micro-powder diamond copper composite substrate with high thermal conductivity. This allows the product to have a high thermal conductivity while maintaining a low density, which also significantly reduces the product cost and expands its practical application value.

[0008] The invention provides a method for preparing a heat-conducting substrate by combining micro-powder diamond and copper. The micro-powder diamond is a part cut off when preparing other regular diamonds, and the regular diamond includes MBD6 diamond. The micro-powder diamond is irregular in shape, with dense grooves on the surface, and no crystal plane of MBD6 diamond exists. Micro-powder diamond and copper powder are used as raw materials, a carbide layer is plated on the surface of the diamond by a molten salt method, and then a vacuum hot pressing method is used to combine the diamond with the copper powder to prepare the heat-conducting substrate.

[0009] The present invention provides a method for preparing a thermally conductive substrate by combining micro-powder diamond and copper, which specifically comprises the following steps:

[0010] S1: Obtaining micro-powder diamond; the micro-powder diamond is waste obtained by cutting regular diamond when preparing regular diamond, and the waste is passed through a sieve to obtain micro-powder diamond of 10 μm to 30 μm.

[0011] S2: The micro-powder diamond is reduced by microwave plasma device in H2 atmosphere; Micro-powder diamond can remove the adsorbed oxygen on the surface of micro-powder diamond under H2 atmosphere, so that micro-powder diamond with dense grooves on the surface can also be plated with Cr3C2 smoothly. It can be seen from the changes in element content before and after microwave treatment in Table 1 that the relative atomic mass of oxygen element is significantly reduced, and Figure 7 The EDS graph in also proves the reduction of oxygen element.

[0012] S3: Mix the reduced micro-powder diamond with a mass fraction of 2 and the chromium powder with a mass fraction of 0.3-0.4, grind an appropriate amount of NaCl and KCl mixed salt and cover it on the mixed powder of micro-powder diamond and chromium powder, perform vacuum sintering, wash to remove the NaCl and KCl mixed salt, and then dry to obtain a diamond with Cr3C2 plated on the surface;

[0013] S4 obtains copper powder, and performs annealing and reduction treatment on the copper powder in a H2 atmosphere to obtain treated copper powder;

[0014] S5 mixes the treated copper powder and the diamond powder coated with Cr3C2 on the surface, and then sinters them in a vacuum hot pressing furnace to obtain a thermal conductive substrate.

[0015] Preferably, in S1, the micro-powder diamond with a particle size of 10 μm to 30 μm is pretreated as follows: the micro-powder diamond with a particle size of 10 μm to 30 μm is cleaned with a sulfuric acid solution in an ultrasonic cleaning device, the acid-washed diamond is neutralized and washed with a sodium hydroxide solution, and then the micro-powder diamond is washed with deionized water; and the micro-powder diamond is placed in a drying oven for drying.

[0016] Preferably, in S2, the microwave power is not less than 800 W, the pressure of the H2 atmosphere is not less than 2.3 kPa, and the reaction time of the reduction treatment is not less than 15 min.

[0017] Preferably, in S3, the mass ratio of NaCl and KCl in the NaCl, KCl mixed salt is 1:1; the vacuum sintering specifically includes: using a vacuum tube furnace, adopting a heating rate of 4°C / min, a vacuum degree of 1×10-3Pa, raising the temperature to 950°C and keeping it for 30 minutes, and then allowing it to cool naturally to room temperature.

[0018] Preferably, in S4, the annealing and reduction treatment of the copper powder under H2 atmosphere specifically includes: annealing and reducing the copper powder in a tube furnace at a temperature of 500°C under H2 atmosphere.

[0019] Preferably, in S5, the treated copper powder and the diamond coated with Cr3C2 on the surface are mixed and then sintered in a vacuum hot pressing furnace, specifically comprising: the mass ratio of the treated copper powder and the diamond coated with Cr3C2 on the surface is 1.7:0.445; the sintering temperature is 850°C, the vertical pressure is 40MPa, and the sintering is carried out under vacuum conditions for 30min. Compared with the prior art, the beneficial effects of the present invention are:

[0020] The present invention uses a unique microwave plasma reduction device to reduce in H2 atmosphere and adopts a molten salt process to prepare surface metallized micro-powder diamond, which is then composited with reduced copper powder to prepare a thermal conductive substrate, providing a way of studying the surface metallization of micro-powder diamond (irregular shape);

[0021] The molten salt method for preparing metallized micro-powder diamond (irregular shape) has simple equipment, convenient operation and low cost. The present invention gives full play to the advantages of low price and small particle size of micro-powder diamond, explores the research of diamond copper composite material thermal conductive substrate, makes thinner and more affordable diamond copper thermal conductive substrate possible, and is more conducive to practical application in the future market. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 In the figure, (a) and (b) are respectively the micro-powder diamond of the present invention and the conventional MBD6 diamond;

[0024] Figure 2 In the figure, (a) and (b) are SEM images of micro-powder diamond particles with a particle size of 10 μm in Example 1 of the present invention; (c) and (d) are SEM images of micro-powder diamond particles with a particle size of 30 μm in Example 2 of the present invention;

[0025] Figure 3 In the figure, (a) is a temperature-variable test performance diagram of different Dia / Cr ratios of 10 μm micro-powder diamond in the present invention; (b) is a temperature-variable test performance diagram of 30 μm micro-powder diamond embodiment and comparative example in the present invention;

[0026] Figure 4 , (a) a low magnification SEM image of the diamond particles used in sample N1 of the present invention; (b) a high magnification SEM image of the diamond particles used in sample N1 of the present invention;

[0027] Figure 5 In the figure, (a) is a low magnification SEM image of the diamond particles used in sample N2 of the present invention; (b) is a high magnification SEM image of the diamond particles used in sample N2 of the present invention;

[0028] Figure 6 The EDS region and corresponding energy spectrum of the diamond particles used in sample N1 of the present invention;

[0029] Figure 7 In the figure, (a) and (b) are respectively the SEM image and O-EDS image before microwave plasma treatment in the present invention;

[0030] (c) and (d) are respectively the SEM image and O-EDS image after microwave plasma treatment in the present invention;

[0031] Figure 8 In the figure, (a) is a SEM image of the diamond particles used in sample M2 of the present invention; (b) is a SEM image of the diamond particles used in sample M2 of the present invention;

[0032] Fig. 9 In the figure, (a) is a SEM image of the diamond particles used in sample M1 of the present invention; (b) is a SEM image of the diamond particles used in sample M1 of the present invention;

[0033] Fig.10 In the figure, (a) is a SEM image of the diamond particles used in sample M3 of the present invention; (b) is a SEM image of the diamond particles used in sample M3 of the present invention;

[0034] Fig.11 In the figure, (a) is a low-magnification SEM image of the diamond particles used in sample M4 of the present invention; (b) is a high-magnification SEM image of the diamond particles used in sample M4 of the present invention;

[0035] Fig.12 EDS area and corresponding energy spectrum of diamond particles used for sample M1;

[0036] Fig.13 In the figure, (a) is a cross-sectional SEM image of M2 in the present invention; (b) is a cross-sectional SEM image of M1 in the present invention; (c) is a cross-sectional SEM image of M3 in the present invention;

[0037] Fig.14 This is the EDS spectrum of the M1 cross section in the present invention;

[0038] Fig.15 This is a backscattered SEM image of Example M1 of the present invention;

[0039] Fig.16 It is the XRD phase analysis diagram of M1, M2 and M3 in the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] A process for preparing a thermally conductive substrate by combining micro-powder diamond and copper powder, characterized in that micro-powder diamond and copper powder are used as raw materials, a carbide layer is plated on the surface of the diamond by a molten salt method, and then a vacuum hot pressing method is used to combine the diamond and copper powder to prepare the thermally conductive substrate.

[0042] A process for preparing a thermally conductive substrate using molten salt and vacuum hot pressing, comprising the following steps:

[0043] Step 1: Clean 10μm and 30μm micro-powder diamonds with 0.5mol / L H2SO4 solution and ultrasonic device for 30 minutes; then use 0.5mol / L NaOH solution to neutralize the cleaned H2SO4 solution and ultrasonic device for 30 minutes; finally, clean twice with deionized water in ultrasonic device for 30 minutes each time.

[0044] Step 2: Place the cleaned micro-powder diamond in a 60°C drying oven and dry for 2-3 hours.

[0045] Step 3: The dried micro-powder diamond is reduced using a microwave plasma device in a H2 atmosphere.

[0046] element Before microwave reduction After microwave reduction C 92.81 94.42 N 3.64 3.95 O 3.55 1.64

[0047] Table 1: Comparison of elements before and after microwave treatment

[0048] Step 4: Take a certain amount of micro-powder diamond and Cr powder in step 2 and mix them in a certain proportion. Take a certain amount of NaCl and KCl mixed salt, grind them and cover the powder.

[0049] Step 5: Take the mixed powder in step 3 and sinter it in a tube furnace. Wash the sintered powder to remove residual salt on the surface.

[0050] Step 6: Take a certain amount of copper powder and anneal it in a tube furnace for pretreatment.

[0051] Step 7: Mix an appropriate amount of powder from step 4 with copper powder, and put the mixed powder into the prepared mold.

[0052] Step 8: Take the mold after mixing the powder in step 6 and sinter it in a high temperature and high pressure furnace.

[0053] By controlling the ratio of the mixed powder in step three, step four is then performed to obtain Cr3C2-coated micro-powder diamond.

[0054] The micro-powder diamond selected in step 1 is diamond powder with a diameter less than 30 μm.

[0055] The diamond in step 2 is dried for 2 to 3 hours to ensure that any residual moisture is removed.

[0056] The microwave power in step 3 should be 800 W; H2 should be passed; the gas pressure should be 2.3 KPa; and the reduction time should be 15 min.

[0057] In step 4, Dia / Cr=2g / 0.4g, and the mixed salt should be NaCl / KCl=1g / 1g.

[0058] The mixed powder in step 5 should be sintered in a tube furnace at 950°C for 30 min.

[0059] In step 6, the copper powder is annealed in a tube furnace at 500° C. for 30 minutes in a H 2 atmosphere for reduction treatment.

[0060] In step eight, the sintering is performed at a temperature of 850° C., a vertical pressure of 40 MPa, and vacuum conditions for 30 minutes.

[0061] Example 1

[0062] Take 20g of diamond powder with a particle size of 10um and place it in 200ml of 0.5mol / L H2SO4 solution for ultrasonic cleaning for 30min. Then place the cleaned diamond powder in 200ml of 0.5mol / L NaOH solution for ultrasonic cleaning for 30min. Finally, wash it twice with deionized pure water for 30min each time and then dry it in an oven for 3h. Take an appropriate amount of dried diamond powder and place it in a microwave plasma device under H2 atmosphere; microwave power 800W; reduce for 15min and wait for natural cooling. Take the cleaned diamond and mix it evenly according to the ratio of Dia / Cr=2 / 0.3(g), then take 1g of NaCl and KCl each, mix and grind, and place the mixed salt powder on the top. Place the quartz crucible containing the mixed powder in a vacuum tube furnace with a heating rate of 4℃ / min and a vacuum degree of 1×10 -3 Pa, raised to 950℃ and kept warm for 30min, then allowed to cool naturally to room temperature. The sintered powder was repeatedly washed in deionized water until the salt was completely washed (the water was clear and free of turbidity). Take 15g of copper powder and reduce it in a tube furnace at 500℃ for 30min through H2 atmosphere. Weigh 0.445g of surface metallized diamond and 1.700g of reduced copper powder on a balance and mix them in a mixer for 1h to mix evenly. A cylindrical sample with a diameter of 12.7mm and a height of 2.5mm was prepared in advance. The mold was kept at 850℃ in a vacuum hot pressing furnace for 60min and then cooled naturally to room temperature. The fired sample was recorded as N1.

[0063] Comparative Case 1

[0064] Take 20g of diamond powder with a particle size of 10um and place it in 200ml of 0.5mol / L H2SO4 solution for ultrasonic cleaning for 30min. Then place the cleaned diamond powder in 200ml of 0.5mol / L NaOH solution for ultrasonic cleaning for 30min. Finally, wash it twice with deionized pure water for 30min each time and then dry it in an oven for 3h. Take an appropriate amount of dried diamond powder and place it in a microwave plasma device under H2 atmosphere; microwave power 800W; reduce for 15min and wait for natural cooling. Take the cleaned diamond and mix it evenly according to the ratio of Dia / Cr=2 / 0.4(g), then take 1g of NaCl and KCl each, mix and grind, and place the mixed salt powder on the top. Place the quartz crucible containing the mixed powder in a vacuum tube furnace with a heating rate of 4℃ / min and a vacuum degree of 1×10 -3 Pa, raised to 950℃ and kept warm for 30min, then allowed to cool naturally to room temperature. The sintered powder was repeatedly washed in deionized water until the salt was completely washed (the water was clear and free of turbidity). Take 15g of copper powder and reduce it in a tube furnace at 500℃ for 30min through H2 atmosphere. Weigh 0.445g of surface metallized diamond and 1.700g of reduced copper powder on a balance and mix them in a mixer for 1h to mix evenly. A cylindrical sample with a diameter of 12.7mm and a height of 2.5mm was prepared in advance. The mold was kept at 850℃ in a vacuum hot pressing furnace for 60min and then cooled naturally to room temperature. The fired sample was recorded as N2.

[0065] Example 2

[0066] Take 20g of diamond powder with a particle size of 30um and place it in 200ml of 0.5mol / L H2SO4 solution for ultrasonic cleaning for 30min. Then place the cleaned diamond powder in 200ml of 0.5mol / L NaOH solution for ultrasonic cleaning for 30min. Finally, wash it twice with deionized pure water for 30min each time and then dry it in an oven for 3h. Take an appropriate amount of dried diamond powder and place it in a microwave plasma device under H2 atmosphere; microwave power 800W; reduce for 15min and wait for natural cooling. Take the cleaned diamond and mix it evenly according to the ratio of Dia / Cr=2 / 0.4(g), then take 1g of NaCl and KCl each, mix and grind, and place the mixed salt powder on the top. Place the quartz crucible containing the mixed powder in a vacuum tube furnace with a heating rate of 4℃ / min and a vacuum degree of 1×10 -3Pa, raised to 950℃ and kept warm for 30min, then allowed to cool naturally to room temperature. The sintered powder was repeatedly washed in deionized water until the salt was completely washed (the water was clear and free of turbidity). Take 15g of copper powder and reduce it in a tube furnace at 500℃ for 30min through H2 atmosphere. Weigh 0.445g of surface metallized diamond and 1.700g of reduced copper powder on a balance and mix them in a mixer for 1h to mix evenly. A cylindrical sample with a diameter of 12.7mm and a height of 2.5mm was prepared. The mold was kept at 850℃ in a vacuum hot pressing furnace for 60min and then cooled naturally to room temperature. The fired sample was recorded as M1.

[0067] Comparative Case 2

[0068] Take 20g of diamond powder with a particle size of 30um and place it in 200ml of 0.5mol / L H2SO4 solution for ultrasonic cleaning for 30min. Then place the cleaned diamond powder in 200ml of 0.5mol / L NaOH solution for ultrasonic cleaning for 30min. Finally, wash it twice with deionized pure water for 30min each time and then dry it in an oven for 3h. Take an appropriate amount of dried diamond powder and place it in a microwave plasma device under H2 atmosphere; microwave power 800W; reduce for 15min and wait for natural cooling. Take the cleaned diamond and mix it evenly according to the ratio of Dia / Cr=2 / 0.3(g), then take 1g of NaCl and KCl each, mix and grind, and place the mixed salt powder on the top. Place the quartz crucible containing the mixed powder in a vacuum tube furnace with a heating rate of 4℃ / min and a vacuum degree of 1×10 -3 Pa, raised to 950℃ and kept warm for 30min, then allowed to cool naturally to room temperature. The sintered powder was repeatedly washed in deionized water until the salt was completely washed (the water was clear and free of turbidity). Take 15g of copper powder and reduce it in a tube furnace at 500℃ for 30min through H2 atmosphere. Weigh 0.445g of surface metallized diamond and 1.700g of reduced copper powder on a balance and mix them in a mixer for 1h to mix evenly. A cylindrical sample with a diameter of 12.7mm and a height of 2.5mm was prepared. The mold was kept at 850℃ in a vacuum hot pressing furnace for 60min and then cooled naturally to room temperature. The fired sample is recorded as M2.

[0069] Comparative Case 3

[0070] Take 20g of diamond powder with a particle size of 30um and place it in 200ml of 0.5mol / L H2SO4 solution for ultrasonic cleaning for 30min. Then place the cleaned diamond powder in 200ml of 0.5mol / L NaOH solution for ultrasonic cleaning for 30min. Finally, wash it twice with deionized pure water for 30min each time and then dry it in an oven for 3h. Take an appropriate amount of dried diamond powder and place it in a microwave plasma device under H2 atmosphere; microwave power 800W; reduce for 15min and wait for natural cooling. Take the cleaned diamond and mix it evenly according to the ratio of Dia / Cr=2 / 0.5(g), then take 1g of NaCl and KCl each, mix and grind, and place the mixed salt powder on the top. Place the quartz crucible containing the mixed powder in a vacuum tube furnace with a heating rate of 4℃ / min and a vacuum degree of 1×10 -3 Pa, raised to 950℃ and kept warm for 30min, then allowed to cool naturally to room temperature. The sintered powder was repeatedly washed in deionized water until the salt was completely washed (the water was clear and free of turbidity). Take 15g of copper powder and reduce it in a tube furnace at 500℃ for 30min through H2 atmosphere. Weigh 0.445g of surface metallized diamond and 1.700g of reduced copper powder on a balance and mix them in a mixer for 1h to mix evenly. A cylindrical sample with a diameter of 12.7mm and a height of 2.5mm was prepared in advance. The mold was kept at 850℃ in a vacuum hot pressing furnace for 60min and then cooled naturally to room temperature. The fired sample was recorded as M3.

[0071] Comparative Case 4

[0072] Take 20g of diamond powder with a particle size of 30um and place it in 200ml of 0.5mol / L H2SO4 solution for ultrasonic cleaning for 30min, then place the cleaned diamond powder in 200ml of 0.5mol / L NaOH solution for ultrasonic cleaning for 30min, finally wash it twice with deionized pure water for 30min each time and then dry it in an oven for 3h. Take the cleaned diamond and mix it evenly according to the ratio of Dia / Cr=2 / 0.4(g), then take 1g of NaCl and KCl each, mix and grind, and place the mixed salt powder on the top. Place the quartz crucible containing the mixed powder in a vacuum tube furnace with a heating rate of 4℃ / min and a vacuum degree of 1×10 -3Pa, raised to 950℃ and kept warm for 30min, then allowed to cool naturally to room temperature. The sintered powder was repeatedly washed in deionized water until the salt was completely washed (the water was clear and free of turbidity). Take 15g of copper powder and reduce it in a tubular furnace at 500℃ for 30min through H2 atmosphere. Weigh 0.445g of surface metallized diamond and 1.700g of reduced copper powder on a balance and mix them in a mixer for 1h to mix evenly. A cylindrical sample with a diameter of 12.7mm and a height of 2.5mm was prepared. The mold was kept at 850℃ for 60min in a vacuum hot pressing furnace and then cooled naturally to room temperature. The fired sample was recorded as M4. The diamond particles used in M4 adopted the optimal ratio of Dia / Cr=2 / 0.4g, but no microwave plasma device was used for H2 reduction. The surface of the sintered Cr-plated micropowder diamond particles had protrusions, pits, and cracks. As Fig.11 (b) is marked with a yellow frame. Fig. 9 Compared with the same ratio in (b) and reduction using microwave plasma device, Fig. 9 (b) The plated layer is flatter and smoother, and can better bond with copper.

[0073] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A method for preparing a thermally conductive substrate by composite of micro-powder diamond and copper, characterized in that: The micro-powder diamond is the part cut off when preparing other regular diamonds, and the regular diamond includes MBD6 diamond; the micro-powder diamond is irregular in shape, with dense grooves on the surface, and there is no crystal face of MBD6 diamond; micro-powder diamond and copper powder are used as raw materials, a carbide layer is plated on the surface of the diamond by a molten salt method, and then a vacuum hot pressing method is used to combine it with copper powder to prepare a thermal conductive substrate.

2. A method for preparing a thermally conductive substrate by composite of micro-powder diamond and copper, characterized in that: The following steps are involved: S1: Obtaining micro-powder diamond; the micro-powder diamond is the waste obtained by cutting regular diamond when preparing regular diamond, and the waste is passed through a sieve to obtain micro-powder diamond of 10 μm to 30 μm; S2: reducing the diamond powder in a H2 atmosphere using a microwave plasma device; S3: Mix the reduced micro-powder diamond with a mass fraction of 2 and the chromium powder with a mass fraction of 0.3-0.4, grind an appropriate amount of NaCl and KCl mixed salt and cover it on the mixed powder of diamond and chromium powder, perform vacuum sintering, and then wash to remove the NaCl and KCl mixed salt, and then dry to obtain a diamond with Cr3C2 plated on the surface; S4 obtains copper powder, and performs annealing and reduction treatment on the copper powder in a H2 atmosphere to obtain treated copper powder; S5 mixes the treated copper powder and the diamond powder coated with Cr3C2 on the surface, and then sinters them in a vacuum hot pressing furnace to obtain a thermal conductive substrate.

3. The method for preparing a thermally conductive substrate by composite of micro-powder diamond and copper as claimed in claim 2, characterized in that: In S1, the micro-powder diamond with a particle size of 10 μm to 30 μm is pretreated as follows: the micro-powder diamond with a particle size of 10 μm to 30 μm is cleaned with a sulfuric acid solution in an ultrasonic cleaning device, the acid-washed diamond is neutralized and washed with a sodium hydroxide solution, and then the micro-powder diamond is washed with deionized water; and the micro-powder diamond is placed in a drying oven for drying.

4. The method for preparing a thermally conductive substrate by composite of micro-powder diamond and copper as claimed in claim 2, characterized in that: In S2, the microwave power is not less than 800 W, the pressure of the H2 atmosphere is not less than 2.3 kPa, and the reaction time of the reduction treatment is not less than 15 min.

5. The method for preparing a thermally conductive substrate by combining micro-powder diamond and copper as claimed in claim 2, characterized in that: In S3, the mass ratio of NaCl and KCl in the NaCl-KCl mixed salt is 1:1; The vacuum sintering specifically includes: using a vacuum tube furnace, adopting a heating rate of 4°C / min, a vacuum degree of 1×10-3Pa, heating to 950°C and maintaining the temperature for 30 minutes, and then naturally cooling the temperature to room temperature.

6. The method for preparing a thermally conductive substrate by combining micro-powder diamond and copper as claimed in claim 2, characterized in that: In S4, the copper powder is subjected to annealing and reduction treatment under H2 atmosphere, which specifically includes: the copper powder is subjected to annealing and reduction treatment at a temperature of 500° C. in a tube furnace with H2 atmosphere.

7. The method for preparing a thermally conductive substrate by combining micro-powder diamond and copper as claimed in claim 2, characterized in that: In S5, the treated copper powder and the diamond with Cr3C2 coated on the surface are mixed and then sintered in a vacuum hot pressing furnace, specifically including: the mass ratio of the treated copper powder and the diamond with Cr3C2 coated on the surface is: 1.7:0.445; the sintering temperature is 850°C, the vertical pressure is 40MPa, and the sintering is carried out under vacuum conditions for 30 minutes.